UJI DAYA TERIMA DAN NILAI GIZI BAKSO DENGAN SUBSTITUSI AMPAS KELAPA DAN BELUT - Rika .; Etti Sudaryati; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Many people are afraid and very rare eat eel because of its disgusting and scary like a snake, although eel rich in nutrients. Therefore, it’s necessary to process the eels into favorite food, one of which is fish meatballs. Eels contains iron and fat is very high so that in making these meatballs added flour coconut pulp that contains a very high fiber, and added sago flour and wheat flour. This research was an experimental with a single treatment. The purpose of this research was to acceptance test covering the taste, aroma, color and texture are determined using hedonic scale and protein content by using Kjeldahl, crude fiber content by using extracted and iron content by using AAS. Panelists in this research were students of the Faculty of Public Health University of North Sumatra as many as 30 people. The results showed that the fish meatballs made from coconut pulp and eels have protein 7,91 %, crude fiber 0,30 % and iron 26,0 mg/kg. Meatballs organoleptic test results based on the assessment of taste and texture result with less like categories, while the aroma and color based on the assessment result with categories like. Use of eel and coconut pulp in making fish meatballs contribute protein, fiber and iron which is good compared with meatballs in general. It’s recommended that the eel and coconut pulp can be utilized in making meatballs as foods rich in iron and fiber and can reduce the environmental impact of the waste coconut pulp. Keyword : Fish Meatballs, Flour Coconut Pulp, Eel